Pelatihan Akuntansi Dasar untuk Meningkatkan Kompetensi Auditor di KAP Sarastanto dan Rekan Kota Semarang - Ratna Herawati; Agung Prajanto; Dian Indriana Hapsari (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Transparency of financial reports today is very wide open with advances in technological development. Openness of financial report information allows the public to assess the quality of financial reports. The quality of good financial reports can be seen from the results of opinions by the public accounting profession who provide services to assess the fairness of financial reports. Fairness of financial reports provides the assumption that the financial reports have been prepared in accordance with the financial accounting standards applicable in Indonesia. Financial Accounting Standards provide guidance on the process of recording, measuring and presenting financial reports. A good financial report must start first with recording the accounting cycle. Understanding an entity's accounting cycle makes the auditor understand the recording and reporting model of a client entity. An accounting cycle that is understood by the auditor will be useful in providing adjustments or audit correction journals if recording errors occur. The community service program carried out by a team of lecturers from the Faculty of Economics and Business, Dian Nuswantoro University with auditors at KAP Sarastanto and Pekan Kota Semarang provides several trainings related to basic accounting knowledge. This activity is expected to provide knowledge and skills in preparing financial reports in accordance with standards